2005
DOI: 10.1201/9781420028324.ch9
|View full text |Cite
|
Sign up to set email alerts
|

When does the equality I2 = QI hold true in Buchsbaum rings?

Abstract: Let A be a Noetherian local ring with the maximal ideal m and d = dim A. Let Q be a parameter ideal in A. Let I = Q : m. The problem of when the equality I 2 = QI holds true is explored. When A is a Cohen-Macaulay ring, this problem was completely solved by A. Corso, C. Huneke, C. Polini, and W. Vasconcelos [CHV, CP, CPV], while nothing is known when A is not a Cohen-Macaulay ring. The present purpose is to show that within a huge class of Buchsbaum local rings A the equality I 2 = QI holds true for all parame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(34 citation statements)
references
References 4 publications
0
34
0
Order By: Relevance
“…Theorem 1.2 (see [CHV], [CP1], [CP2], [CPV], [G2] This result has led to two directions of research to better understand the quasi-socle ideals I = Q : m q in arbitrary local rings. One direction is to weaken the assumption on base rings A, which was performed by the first and the third authors (see [GSa1], [GSa2], [GSa3]). They explored the socle ideals I = Q : m inside Buchsbaum local rings A and showed that I 2 = QI and that G(I) is a Buchsbaum ring if e 0 m (A) ≥ 2 and if Q is contained in a sufficiently high power of the maximal ideal m. The other direction was independently performed by Wang [Wan] and also by the first author, Matsuoka, Takahashi, Kimura, Phuong, and Truong (see [GMT], [GKM], [GKMP], [GKPT]).…”
Section: Here M = Mg(i) + G(i) + and [H I M (G(i))] N (I N ∈ Z) Denomentioning
confidence: 99%
“…Theorem 1.2 (see [CHV], [CP1], [CP2], [CPV], [G2] This result has led to two directions of research to better understand the quasi-socle ideals I = Q : m q in arbitrary local rings. One direction is to weaken the assumption on base rings A, which was performed by the first and the third authors (see [GSa1], [GSa2], [GSa3]). They explored the socle ideals I = Q : m inside Buchsbaum local rings A and showed that I 2 = QI and that G(I) is a Buchsbaum ring if e 0 m (A) ≥ 2 and if Q is contained in a sufficiently high power of the maximal ideal m. The other direction was independently performed by Wang [Wan] and also by the first author, Matsuoka, Takahashi, Kimura, Phuong, and Truong (see [GMT], [GKM], [GKMP], [GKPT]).…”
Section: Here M = Mg(i) + G(i) + and [H I M (G(i))] N (I N ∈ Z) Denomentioning
confidence: 99%
“…Let M be a finitely-generated d-dimensional A-module with finite local cohomologies. Then we have the following inequalities: In two recent papers [8,9], Goto with H. Sakurai has returned to the study of the index of reducibility of parameter ideals in order to investigate when the equality I 2 = QI holds for a parameter ideal Q in A, where I = (Q : A m). According to earlier research of A. Corso, C. Huneke, C. Polini, and W. Vasconcelos [2][3][4], this equality holds for all parameter ideals Q in case A is a Cohen-Macaulay ring which is not regular.…”
Section: Introductionmentioning
confidence: 98%
“…Set I = (Q : R n). Then according to [GSa,Proposition 2.3], we have that nI = nQ. Since a ∈ I, na ⊆ nI = nQ = nay 1 .…”
Section: Proposition 41 [Eg Theorem A]mentioning
confidence: 99%
“…In 2003, Goto and H. Sakurai showed that if M is Buchsbaum (i.e., m is a standard ideal for M), then there exists a power of m inside which every parameter ideal for M has the same index of reducibility on M [GSa,Corollary 3.13], necessarily equal to the lower bound of the Goto-Suzuki type. We refer to this by saying M has eventual constant index of reducibility of parameter ideals.…”
Section: Introductionmentioning
confidence: 99%